Pengenalan Aeromodelling Berbasis IT Untuk Menumbuhkan Jiwa Wirausaha Dan Prestasi Di SMK NU Tarub Tegal - Jatmiko Indriyanto; Wildani Eko Nugroho; Nurohim (LPPM Universitas PGRI Adi Buana Surabaya, 2021)
The basic problem of SMK graduates is that most are still looking for work in companies, because the number of SMK graduates is not comparable to the employment opportunities in companies, so many are unemployed. Unemployment is open at the level of SMK graduates is still high. The results of an analysis of the economic potential of the open unemployment data in 2015 showed that over one third or 36.78% of vocational school graduates were still unemployed. Education and training for job seekers has not been maximally organized by the Tegal City Government to encourage them to become new entrepreneurs (WUB). There are still many vocational students who have difficulty getting into state universities because of lack of achievement. The government has provided a path of achievement, the selection process focuses on academic and non-academic achievements during high school / equivalent Seeing the above problems, the introduction of IT-based Aeromodelling to Grow Entrepreneurial Soul and Achievement, can increase student interest to switch his mind to try entrepreneurship and achievement. The introduction of IT-based Aeromodelling for Growing an Entrepreneurial Soul and Achievement turned out to be able to, increase students' interest in entrepreneurship and achievement in non-academic fields.